PEMAHAMAN MASYARAKAT TENTANG PEMANFAATAN DAN FUNGSI PEKARANGAN MENDUKUNG DIVERSIFIKASI PANGAN DI DESA LENDOLA-KABUPATEN ALOR - Didiana Yanuarita Molebila (JURNAL AGRIBISAINS, 2022)
The purpose of this study was to determine community perceptions about the use and function of the yard to support food diversification in Lendola Village, Teluk Mutiara District. This research was conducted from April to August 2020 in Lendola Village, Teluk Mutiara sub-district.The sample was determined deliberately for the sake of research needs and based on several criteria, namely having a yard area ≥ 100 m2 planted with various plants, length of stay ≥ 3 years, age ≥ 30 years and female. There are two main variables observed, namely the characteristics of respondents based on the level of education, the community's understanding of the benefits and functions of the yard. Data were analyzed quantitatively and qualitatively and presented in tables and figures. The results showed that most respondents only graduated from elementary school (SD). But in understanding the benefits and functions of the yard, in general most of the people have understood it well. The community has benefited from the yard, and also 94.87% of the community understands the benefits of the yard as a source of family nutrition. However, the community needs counseling related to the importance of the benefits of the yard to support food diversification. Even so, 89.74% of the people understand the function of the yard as a source of family food to support food diversification in fulfilling family nutrition. In addition, the community also understands the function of the yard as a source of beauty, a tool for social interaction with neighbors, even as a source of family income.